Solventless oil extractor using reduced pressure and heat - Nor Munirah Che Othman (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The materials and methods used for the distillation and extraction of the essential oil from orange rinds by solventless oil extractor using reduced pressure and heat was described in detailed. The extraction begins with the preparation of the sample, equipment set-up and experimental operation. This will involve direct extraction from orange rinds without solvent by reduced pressure and heat to obtain the oil then extracting the oil from the water. The percentage of limonene is over 90 % for every treatment that has been analyzed by Gas Chromatography. It shows that by extraction without solvent, percentage of limonene was approximately the same as solvent extraction. Percentage yield of essential oil per mass of orange rinds used for Treatment 3 was the highest yield with 3.877 % compared to other treatments. The data and observation has shown that by extraction without solvent, the smell of orange scent is strong and best for longer remaining time. The essential oil produced is colorless and there is no need of purification step. The purity of oil is preserved, an environmentally friendly and has a low cost due to simple step compared to extraction with solvent technique that has multistep.